O-GlcNAcylation of RIPK1 rescues red blood cells from necroptosis - Seo, Junghwa; Kim, Yeolhoe; Ji, Suena; Kim, Han Byeol; Jung, Hyeryeon; Yi, Eugene C.; Lee, Yong-ho; Shin, Injae; Yang, Won Ho; Cho, Jin Won (Frontiers in Immunology, 2023)
Necroptosis is a type of cell death with excessive inflammation and organ damage in various human diseases. Although abnormal necroptosis is common in patients with neurodegenerative, cardiovascular, and infectious diseases, the mechanisms by which O-GlcNAcylation contributes to the regulation of necroptotic cell death are poorly understood. In this study, we reveal that O-GlcNAcylation of RIPK1 (receptor-interacting protein kinase1) was decreased in erythrocytes of the mouse injected with lipopolysaccharide, resulting in the acceleration of erythrocyte necroptosis through increased formation of RIPK1-RIPK3 complex. Mechanistically, we discovered that O-GlcNAcylation of RIPK1 at serine 331 in human (corresponding to serine 332 in mouse) inhibits phosphorylation of RIPK1 at serine 166, which is necessary for the necroptotic activity of RIPK1 and suppresses the formation of the RIPK1-RIPK3 complex in Ripk1-/- MEFs. Thus, our study demonstrates that RIPK1 O-GlcNAcylation serves as a checkpoint to suppress necroptotic signaling in erythrocytes.